The impact of language sciences in the of jurisprudence - Alami, Abdullah (Journal of Islamic Sciences, 2018)
This research examines the impact of language science on the development of jurisprudence, an attempt to link the linguistic lesson with the study of Sharia. The research proceeded according to the following plan: It began by revealing the relationship between the sciences of language and the sciences of Shari'a by showing the close connection between the science of rhetoric and the fundamentals of fiqh, which are the core of the linguistic and legal lesson.The study was used to download the language sciences in the analysis of the legal texts, where the researcher applied the data of the linguistic lesson on the texts of the provisions to explain the essential role of these sciences in the allocation of the rule, and weighting of diligence.
Keywords: Language Sciences; Jurisprudence